Preparation method of graphitized cathode

In the preparation process of graphitized cathode carbon blocks, the embedded structure formation technology of precalcination, crushing, mixing and binder is used to solve the problem of high sulfur content in the raw materials of high sulfur petroleum coke and medium sulfur petroleum coke, and the strength and service life of graphitized cathode carbon blocks are significantly improved.

CN119528577APending Publication Date: 2025-02-28ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411742405.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When high-sulfur petroleum coke and medium-sulfur petroleum coke are used as raw materials, how to increase the strength of graphitized cathode carbon blocks to extend the service life of the carbon cathode material for aluminum.

Method used

By performing the first pre-calcination and the second pre-calcination, the sulfur content of the high-sulfur petroleum coke and the medium-sulfur petroleum coke respectively, calcined high-sulfur petroleum coke and calcined medium-sulfur petroleum coke with a sulfur content of less than 0.8%. Then it is crushed and mixed to form a low-sulfur content aggregate coke and powder, combined with a binder to form an embedded structure, followed by gradient calcination and graphitization to form dense carbides.

Benefits of technology

It significantly improves the strength of graphitized cathode carbon blocks, extends the service life of the carbon cathode material for aluminum, and reduces the heat generated during the use of the electrolytic cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528577A_ABST
    Figure CN119528577A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of carbon cathodes for aluminum, in particular to a preparation method of a graphitized cathode. The preparation method comprises the following steps: pre-calcining high-sulfur petroleum coke for the first time to obtain calcined high-sulfur petroleum coke; pre-calcining the medium-sulfur petroleum coke for the second time to obtain calcined medium-sulfur petroleum coke; crushing the calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke, and then mixing the crushed high-sulfur petroleum coke and the crushed medium-sulfur petroleum coke to obtain a dry material; mixing an adhesive and the dry material to obtain a cathode raw material; molding the cathode raw material to obtain a cathode raw material block; and carrying out gradient roasting and graphitization treatment on the cathode raw material block to obtain the graphitized cathode carbon block. According to the preparation method, the high-sulfur petroleum coke and the medium-sulfur petroleum coke are treated in a first calcination mode and a second calcination mode respectively, and compact carbides are formed through crushing and mixing treatment and the bonding effect of an adhesive and through gradient roasting and graphitization treatment, so that the strength of the graphitized cathode carbon block can be improved to 23 MPa or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparing carbon cathodes for aluminum, and in particular to a method for preparing a graphitized cathode. Background Art

[0002] Carbon cathode material for aluminum is an important component of the electrolytic cell. It is generally a cathode material composed of aggregate coke particles, powder and asphalt as raw materials. Aggregate coke particles and powder generally use calcined low-sulfur petroleum coke particles. During the roasting process of carbon cathode material for aluminum, the powder and asphalt of calcined low-sulfur petroleum coke particles will form a bonding matrix, thereby connecting the aggregates together. Therefore, calcined petroleum coke is an important raw material for the production of carbon cathode material for aluminum. The quality of the properties of calcined petroleum coke has a great influence on the quality of the cathode. However, with the rapid development of the aluminum industry, the demand for high-quality low-sulfur petroleum coke is increasing. However, the supply of high-quality low-sulfur petroleum coke is showing a downward trend with the continuous development of energy demand, which makes the production quality of carbon cathode material for aluminum deteriorate and cannot meet the production demand of carbon cathode material for aluminum.

[0003] High-sulfur petroleum coke has the advantages of high tap density and high hardness. It can partially replace low-sulfur petroleum coke to produce graphitized cathode carbon blocks. The mix of high-sulfur petroleum coke and medium-sulfur petroleum coke can improve the wear resistance and corrosion resistance of graphitized cathode carbon blocks, extend the service life of graphitized cathode carbon block electrolytic cells, and greatly promote the improvement of various technical and economic indicators of large-scale cell production. However, the strength of the graphitized cathode carbon blocks prepared by the current mix and match is relatively low, which shortens the service life of carbon cathode materials for aluminum. Summary of the invention

[0004] The present application provides a method for preparing a graphitized cathode to solve the following technical problem: how to improve the strength of a graphitized cathode carbon block when high-sulfur petroleum coke and medium-sulfur petroleum coke are used as raw materials.

[0005] In a first aspect, the present application provides a method for preparing a graphitized cathode, the preparation method comprising:

[0006] The high-sulfur petroleum coke is subjected to a first pre-calcination to reduce the sulfur content of the high-sulfur petroleum coke to obtain calcined high-sulfur petroleum coke; wherein the weight of the sulfur in the calcined high-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined high-sulfur petroleum coke;

[0007] The medium-sulfur petroleum coke is subjected to a second pre-calcination to reduce the sulfur content of the medium-sulfur petroleum coke to obtain calcined medium-sulfur petroleum coke; wherein the weight of the sulfur in the calcined medium-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined medium-sulfur petroleum coke;

[0008] The calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke are crushed respectively;

[0009] The crushed calcined high-sulfur petroleum coke and the crushed calcined medium-sulfur petroleum coke are mixed to obtain a dry material containing aggregate coke particles and powder;

[0010] Mixing the binder and the dry material to obtain a cathode raw material;

[0011] Forming the cathode raw material to obtain a cathode raw material block; and

[0012] The cathode raw material block is subjected to gradient calcination and graphitization treatment to obtain a graphitized cathode carbon block.

[0013] Optionally, the temperature of the first pre-baking is 1400° C. to 1600° C., and the time of the first pre-baking is 2 h to 4 h; and / or

[0014] The temperature of the second pre-baking is 1300° C. to 1350° C., and the time of the second pre-baking is 2 h to 4 h.

[0015] Optionally, the weight of sulfur in the high-sulfur petroleum coke is 3% to 7% of the total weight of the high-sulfur petroleum coke; and / or

[0016] The weight of sulfur in the medium-sulfur petroleum coke is 1.5% to 3.0% of the total weight of the medium-sulfur petroleum coke.

[0017] Optionally, the calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke are crushed separately, comprising the steps of:

[0018] The calcined high-sulfur petroleum coke is subjected to a first crushing and a first screening to obtain calcined high-sulfur petroleum coke coarse particles and calcined high-sulfur petroleum coke fine particles, respectively;

[0019] The calcined medium-sulfur petroleum coke is subjected to a second crushing and a second screening to obtain calcined medium-sulfur petroleum coke particles and calcined medium-sulfur petroleum coke powder, respectively.

[0020] Optionally, the average particle size of the calcined high-sulfur petroleum coke coarse particles is 5 mm to 8 mm; and / or

[0021] The average particle size of the calcined high-sulfur petroleum coke fine particles is 2 mm to 5 mm; and / or

[0022] The average particle size of the calcined sulfur petroleum coke particles is 0.3 mm to 2.0 mm; and / or

[0023] The average particle size of the calcined sulfur petroleum coke powder is ≤0.3 mm.

[0024] Optionally, the crushed calcined high-sulfur petroleum coke and the crushed calcined medium-sulfur petroleum coke are mixed to obtain a dry material containing aggregate coke particles and powder, comprising the steps of:

[0025] The calcined high-sulfur petroleum coke coarse particles, the calcined high-sulfur petroleum coke fine particles and the calcined medium-sulfur petroleum coke particles are mixed to obtain aggregate coke particles;

[0026] Stirring and dispersing the calcined medium-sulfur petroleum coke powder to obtain a powder;

[0027] The aggregate char particles and the powder are mixed to obtain dry material.

[0028] Optionally, the weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=(15-20):(20-25):(30-35):100; and / or

[0029] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=(30-35):100; and / or

[0030] The binder includes coal tar; and / or

[0031] The added amount m6 of the binder and the total weight m4 of the dry material satisfy the relationship: m6:m4=(16-18):100.

[0032] Optionally, the step of subjecting the cathode raw material block to gradient calcination and graphitization to obtain a graphitized cathode carbon block comprises the following steps:

[0033] The cathode raw material block is subjected to a first round of calcination to obtain a primary cathode calcined block;

[0034] The primary cathode calcined block is subjected to a second round of calcination to obtain a cathode calcined block;

[0035] The cathode calcined block is graphitized to obtain a graphitized cathode carbon block.

[0036] Optionally, the temperature of the first round of calcination is 1000° C. to 1050° C., and the time of the first round of calcination is 500 h to 600 h; and / or

[0037] The temperature of the second round of calcination is 900° C. to 950° C., and the time of the second round of calcination is 350 h to 400 h; and / or

[0038] The temperature of the graphitization treatment is 2600° C. to 2800° C., and the time of the graphitization treatment is 20 h to 30 h.

[0039] Optionally, the molding process includes kneading and vibration molding; wherein the kneading temperature is 170° C. to 185° C., and the kneading time is 30 min to 60 min; and / or

[0040] The temperature of the vibration molding is 160° C. to 165° C., and the time of the vibration molding is 2 min to 5 min.

[0041] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0042] A method for preparing a graphitized cathode is provided in an embodiment of the present application. The method converts the sulfur of high-sulfur petroleum coke and medium-sulfur petroleum coke into sulfur-containing volatile substances through a first calcination and a second calcination, respectively, so that most of the sulfur is removed from the high-sulfur petroleum coke and the medium-sulfur petroleum coke, thereby obtaining calcined high-sulfur petroleum coke and calcined medium-sulfur petroleum coke with a sulfur weight content of less than 0.8%, respectively. After crushing and mixing, the calcined high-sulfur petroleum coke and calcined medium-sulfur petroleum coke with a low sulfur content can obtain aggregate coke particles and powder with a low sulfur content and high strength, respectively. These aggregate coke particles and powder are then used to prepare graphitized cathode carbon blocks. During the preparation process, the powder with a low sulfur content can be embedded in the aggregate coke particles with a low sulfur content, and then a stable, low-sulfur and high-strength embedded structure is formed between the powder and the aggregate coke particles through the bonding effect of the binder. The embedded structure will be tightly combined in the subsequent gradient roasting and graphitization treatment stages to form a dense carbide, thereby improving the strength of the graphitized cathode carbon block. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0045] Figure 1 A schematic diagram of a method for preparing a graphitized cathode provided in an embodiment of the present application;

[0046] Figure 2 A schematic diagram of a detailed process of preparing a graphitized cathode provided in an embodiment of the present application. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0048] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0049] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions, refers to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0050] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.

[0051] Figure 1 The present invention provides a schematic diagram of a method for preparing a graphitized cathode.

[0052] like Figure 1 As shown, the present application embodiment provides a method for preparing a graphitized cathode, the preparation method comprising:

[0053] S1. Precalcining the high-sulfur petroleum coke for the first time to reduce the sulfur content of the high-sulfur petroleum coke to obtain calcined high-sulfur petroleum coke; wherein the weight of the sulfur in the calcined high-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined high-sulfur petroleum coke;

[0054] S2. subjecting the medium-sulfur petroleum coke to a second pre-calcination to reduce the sulfur content of the medium-sulfur petroleum coke to obtain calcined medium-sulfur petroleum coke; wherein the weight of the sulfur in the calcined medium-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined medium-sulfur petroleum coke;

[0055] S3. The calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke are crushed separately;

[0056] S4. The crushed calcined high-sulfur petroleum coke and the crushed calcined medium-sulfur petroleum coke are mixed to obtain a dry material containing aggregate coke particles and powder;

[0057] S5. Mixing the binder and the dry material to obtain a cathode raw material;

[0058] S6. forming the cathode raw material to obtain a cathode raw material block; and

[0059] S7. The cathode raw material block is subjected to gradient calcination and graphitization treatment to obtain a graphitized cathode carbon block.

[0060] It should be noted that the mixing of the binder and the dry material can be carried out in a mixer.

[0061] It should be noted that the mixing temperature of the binder and the dry material can be 170°C to 180°C.

[0062] In some optional embodiments, the temperature of the first pre-baking is 1400° C. to 1600° C., and the time of the first pre-baking is 2 h to 4 h; and / or

[0063] The temperature of the second pre-baking is 1300° C. to 1350° C., and the time of the second pre-baking is 2 h to 4 h;

[0064] In these embodiments, the temperature of the first pre-baking can be 1400°C to 1600°C, and the time of the first pre-baking can be 2h to 4h. Through the first pre-baking, the sulfur weight content of the high-sulfur petroleum coke is reduced to less than 0.8%, and the calcined high-sulfur petroleum coke with a low sulfur content can be crushed and mixed to obtain low-sulfur aggregate coke particles, and high-strength graphitized cathode carbon blocks can be obtained in the subsequent gradient calcination and graphitization treatment stages; in addition, the temperature of the second pre-baking can be 1300°C to 1350°C, and the time of the second pre-baking can be 2h to 4h. Through the second pre-baking, the sulfur weight content of the medium-sulfur petroleum coke is reduced to less than 0.8%, and the calcined medium-sulfur petroleum coke with a low sulfur content can be crushed and mixed to obtain low-sulfur aggregate coke particles and powder, and high-strength graphitized cathode carbon blocks can be obtained in the subsequent gradient calcination and graphitization treatment stages.

[0065] The temperature of the first pre-baking may be 1400°C, 1450°C, 1500°C, 1550°C or 1600°C.

[0066] The first pre-baking time can be 2.0 h, 2.5 h, 3.0 h, 3.5 h or 4.0 h.

[0067] The temperature of the second pre-baking may be 1300°C, 1310°C, 1320°C, 1330°C, 1340°C or 1350°C.

[0068] The second pre-baking time can be 2.0 h, 2.5 h, 3.0 h, 3.5 h or 4.0 h.

[0069] In some optional embodiments, the weight of sulfur in the high-sulfur petroleum coke is 3% to 7% of the total weight of the high-sulfur petroleum coke; and / or

[0070] The weight of sulfur in the medium-sulfur petroleum coke is 1.5% to 3.0% of the total weight of the medium-sulfur petroleum coke;

[0071] In these embodiments, the weight of sulfur in the high-sulfur petroleum coke can be 3% to 7% of the total weight of the high-sulfur petroleum coke, and the weight of sulfur in the medium-sulfur petroleum coke can be 1.5% to 3.0% of the total weight of the medium-sulfur petroleum coke, which can cover most of the high-sulfur petroleum coke and medium-sulfur petroleum coke, so that the method provided in the embodiments of the present application can cover the existing high-sulfur petroleum coke and medium-sulfur petroleum coke, and improve the universality of the method provided in the embodiments of the present application.

[0072] The weight of sulfur in the high-sulfur petroleum coke may be 3%, 4%, 5%, 6% or 7% of the total weight of the high-sulfur petroleum coke.

[0073] The weight of sulfur in the medium-sulfur petroleum coke can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0% of the total weight of the medium-sulfur petroleum coke.

[0074] Figure 2 The detailed schematic diagram of the preparation method of a graphitized cathode provided in an embodiment of the present application is exemplarily shown;

[0075] In some optional embodiments, such as Figure 2 As shown, the calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke are crushed and mixed respectively to obtain a dry material containing aggregate coke particles and powder, including the steps of:

[0076] S301. performing a first crushing and a first screening on the calcined high-sulfur petroleum coke to obtain calcined high-sulfur petroleum coke coarse particles and calcined high-sulfur petroleum coke fine particles, respectively;

[0077] S302. performing a second crushing and a second screening on the calcined medium-sulfur petroleum coke to obtain calcined medium-sulfur petroleum coke particles and calcined medium-sulfur petroleum coke powder, respectively;

[0078] In these embodiments, calcined high-sulfur petroleum coke and calcined medium-sulfur petroleum coke are subjected to a first crushing and a first screening and a second crushing and a second screening to obtain calcined high-sulfur petroleum coke coarse particles, calcined high-sulfur petroleum coke fine particles and calcined medium-sulfur petroleum coke particles with uniform particle size distribution. The calcined high-sulfur petroleum coke coarse particles, calcined high-sulfur petroleum coke fine particles and calcined medium-sulfur petroleum coke particles with uniform particle size distribution can be used to obtain higher-strength aggregate coke particles through subsequent mixing, and calcined medium-sulfur petroleum coke powder can be used to prepare higher-strength powder. The higher-strength aggregate coke particles and higher-strength powder can improve the overall strength of the dry material to ultimately obtain a high-strength graphitized cathode carbon block.

[0079] In some optional embodiments, the average particle size of the calcined high-sulfur petroleum coke coarse particles is 5 mm to 8 mm; and / or

[0080] The average particle size of the calcined high-sulfur petroleum coke fine particles is 2 mm to 5 mm; and / or

[0081] The average particle size of the calcined sulfur petroleum coke particles is 0.3 mm to 2.0 mm; and / or

[0082] The average particle size of the calcined sulfur petroleum coke powder is ≤0.3 mm;

[0083] In these embodiments, the average particle size of the calcined high-sulfur petroleum coke coarse particles can be 5mm to 8mm, the average particle size of the calcined high-sulfur petroleum coke fine particles can be 2mm to 5mm, and the average particle size of the calcined medium-sulfur petroleum coke particles can be 0.3mm to 2.0mm. The finer calcined medium-sulfur petroleum coke particles and the calcined high-sulfur petroleum coke fine particles can be embedded in the coarser calcined high-sulfur petroleum coke coarse particles to obtain relatively dense aggregate coke particles, which can effectively improve the strength of the graphitized cathode carbon block. In addition, the average particle size of the calcined medium-sulfur petroleum coke powder is ≤0.3mm, which promotes sufficient mixing between the calcined medium-sulfur petroleum coke powder and the low-sulfur petroleum coke to obtain relatively dense powder, which can effectively improve the strength of the graphitized cathode carbon block.

[0084] The average particle size of the calcined high-sulfur petroleum coke coarse particles can be 5 mm, 6 mm, 7 mm or 8 mm.

[0085] The average particle size of the calcined high-sulfur petroleum coke fine particles may be 2 mm, 3 mm, 4 mm or 5 mm.

[0086] The average particle size of the calcined medium-sulfur petroleum coke particles can be 0.3 mm, 0.5 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm or 2.0 mm.

[0087] In some optional embodiments, the crushed calcined high-sulfur petroleum coke and the crushed calcined medium-sulfur petroleum coke are mixed to obtain a dry material containing aggregate coke particles and powder, comprising the steps of:

[0088] S401. The calcined high-sulfur petroleum coke coarse particles, the calcined high-sulfur petroleum coke fine particles and the calcined medium-sulfur petroleum coke particles are mixed to obtain aggregate coke particles;

[0089] S402. The calcined sulfur petroleum coke powder is stirred and dispersed to obtain a powder;

[0090] S403. The aggregate char particles and the powder are mixed to obtain a dry material;

[0091] In these embodiments, calcined high-sulfur petroleum coke coarse particles, calcined high-sulfur petroleum coke fine particles and calcined medium-sulfur petroleum coke particles are mixed to obtain high-strength aggregate coke particles; in addition, after calcined medium-sulfur petroleum coke powder is stirred and dispersed, a powder with uniform particle size distribution and higher strength can be obtained.

[0092] It should be noted that, according to the particle size distribution of the target product, the target particle size of the first crushing is greater than the target particle size of the second crushing, so that calcined high-sulfur petroleum coke coarse particles, calcined high-sulfur petroleum coke fine particles, calcined medium-sulfur petroleum coke particles and calcined medium-sulfur petroleum coke powder with uniform and reasonable particle size distribution can be obtained respectively.

[0093] It should be noted that the temperature of the mixture of the aggregate char particles and the powder can be 150°C to 160°C.

[0094] In some optional embodiments, the weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=(15-20):(20-25):(30-35):100; and / or

[0095] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=(30-35):100; and / or

[0096] The binder includes coal tar; and / or

[0097] The amount of the binder added m6 and the total weight of the dry material m4 satisfy the relationship: m6:m4=(16-18):100;

[0098] In these embodiments, the weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles, and the total weight m4 of the aggregate coke particles can satisfy the relationship: m1:m2:m3:m4=(15-20):(20-25):(30-35):100. By adjusting the mass ratio of the calcined high-sulfur petroleum coke coarse particles, the calcined high-sulfur petroleum coke fine particles, and the calcined medium-sulfur petroleum coke particles, the strength of the aggregate coke particles obtained by mixing the three can be improved, so as to ultimately improve the strength of the graphitized cathode carbon block. In addition, the weight m4 and the calcined medium-sulfur petroleum coke powder are The total weight m5 of the powder can satisfy the relationship: m4:m5=(30~35):100. By adjusting the proportion of calcined medium-sulfur petroleum coke powder in the powder, the strength of the powder is improved by calcining the medium-sulfur petroleum coke powder, so as to ultimately improve the strength of the graphitized cathode carbon block. In addition, the binder can include coal tar, and the amount of the binder added can be 16%~17% of the weight of the cathode raw material, so that the cathode raw material has a sufficient amount of binder. The sufficient amount of binder can promote a firm bond between the aggregate coke particles and the powder, thereby effectively improving the strength of the graphitized cathode carbon block through high-strength aggregate coke particles and powder.

[0099] The weight m1 of the calcined high-sulfur petroleum coke coarse particles can be 15, 16, 17, 18, 19 or 20.

[0100] The weight m2 of the calcined high-sulfur petroleum coke fine particles can be 20, 21, 22, 23, 24 or 25.

[0101] The weight m3 of the calcined sulfur petroleum coke particles can be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.

[0102] The weight m5 of the calcined sulfur petroleum coke powder can be 30, 31, 32, 33, 34 or 35.

[0103] The amount m6 of the binder added may be 16.0, 16.1, 16.2, 16.3, 16.4, 16.5, 16.6, 16.7, 16.8, 16.9, 17.0, 17.1, 17.2, 17.3, 17.4, 17.5, 17.6, 17.7, 17.8, 17.9 or 18.0.

[0104] In some optional embodiments, the cathode raw material block is subjected to gradient calcination and graphitization treatment to obtain a graphitized cathode carbon block, comprising the steps of:

[0105] S701. The cathode raw material block is subjected to a first round of calcination to obtain a primary cathode calcined block;

[0106] S702. The primary cathode calcined block is subjected to a second round of calcination to obtain a cathode calcined block;

[0107] S703. The cathode calcined block is graphitized to obtain a graphitized cathode carbon block;

[0108] In these embodiments, the cathode raw material block is effectively sintered completely through the gradient calcination of the first calcination round and the second calcination round, so that a completely carbonized cathode calcined block can be obtained, which is convenient for subsequent graphitization treatment to obtain a graphitized cathode carbon block.

[0109] In some optional embodiments, the temperature of the first round of calcination is 1000° C. to 1050° C., and the time of the first round of calcination is 500 h to 600 h; and / or

[0110] The temperature of the second round of calcination is 900° C. to 950° C., and the time of the second round of calcination is 350 h to 400 h; and / or

[0111] The temperature of the graphitization treatment is 2600° C. to 2800° C., and the time of the graphitization treatment is 20 h to 30 h;

[0112] In these embodiments, the temperature of the first round of calcination can be 1000°C to 1050°C, and the time of the first round of calcination can be 500h to 600h, so that the material of the cathode raw material block can obtain a preliminary carbonized cathode calcined block through the first round of calcination; in addition, the temperature of the second round of calcination can be 2600°C to 2800°C, and the time of the second round of calcination can be 350h to 400h, so that the material of the primary cathode calcined block can obtain a completely carbonized cathode calcined block through the second round of calcination; in addition, the temperature of the graphitization treatment can be 2600°C to 2800°C, and the time of the graphitization treatment can be 20h to 30h, and the cathode calcined block can be fully converted into a graphitized cathode carbon block through the graphitization treatment.

[0113] The temperature of the first calcination may be 1000°C, 1010°C, 1020°C, 1030°C, 1040°C or 1050°C.

[0114] The time of the first round of roasting can be 500h, 510h, 520h, 530h, 540h, 550h, 560h, 570h, 580h, 590h or 600h.

[0115] The temperature of the second calcination may be 900°C, 910°C, 920°C, 930°C, 940°C or 950°C.

[0116] The time of the second round of roasting can be 350h, 360h, 370h, 380h, 390h or 400h.

[0117] The temperature of the graphitization treatment can be 2600°C, 2610°C, 2620°C, 2630°C, 2640°C, 2650°C, 2660°C, 2670°C, 2680°C, 2690°C, 2700°C, 2710°C, 2720°C, 2730°C, 2740°C, 2750°C, 2760°C, 2770°C, 2780°C, 2790°C or 2800°C.

[0118] The graphitization treatment time can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h or 30h.

[0119] In some optional embodiments, the molding process includes kneading and vibration molding; wherein the kneading temperature is 170° C. to 185° C., and the kneading time is 30 min to 60 min; and / or

[0120] The temperature of the vibration molding is 160°C to 165°C, and the time of the vibration molding is 2min to 5min;

[0121] In these embodiments, the molding process may include kneading and vibration molding, and the kneading temperature may be 170°C to 185°C, and the kneading time may be 30min to 60min, and the cathode raw material is kneaded into shape by kneading to obtain a cathode raw material paste; in addition, the vibration molding temperature may be 160°C to 165°C, and the vibration molding time may be 2min to 5min, and the cathode raw material paste may be formed into a cathode raw material block by vibration molding.

[0122] The kneading temperature may be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C.

[0123] The kneading time can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.

[0124] The vibration molding temperature may be 160°C, 161°C, 162°C, 163°C, 164°C, or 165°C.

[0125] The vibration molding time can be 2 minutes, 3 minutes, 4 minutes or 5 minutes.

[0126] It should be noted that the vibration molding can be performed in a vibration molding machine.

[0127] In summary, the present invention provides a method for preparing a graphitized cathode, which has the following technical advantages:

[0128] 1. Improved strength: Through carefully designed preparation steps, especially the key steps of pre-calcination, crushing and mixing, molding, gradient roasting and graphitization treatment of high-sulfur petroleum coke and medium-sulfur petroleum coke, the strength of the final graphitized cathode carbon block reaches more than 20MPa, which is significantly better than the traditional preparation method.

[0129] 2. Sulfur content control: Through two-stage pre-calcination treatment, the weight of sulfur in high-sulfur petroleum coke and low-sulfur petroleum coke is effectively reduced, thereby improving the purity and performance of the final graphitized cathode carbon block product.

[0130] 3. Process optimization: The entire preparation process has clear steps, simple operation, and close connection between each step, ensuring the quality and performance of the final product.

[0131] Therefore, the graphitized cathode preparation method proposed in this application achieves a significant improvement in the strength of the graphitized cathode carbon block through innovative process design and technical means, providing a new development direction and idea for the technical field of carbon cathode preparation for aluminum.

[0132] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples where specific conditions are not specified are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions or conditions recommended by the manufacturer.

[0133] Example 1

[0134] like Figure 2 As shown, a method for preparing a graphitized cathode comprises:

[0135] S1. Precalcining the high-sulfur petroleum coke for the first time to reduce the sulfur content of the high-sulfur petroleum coke to obtain calcined high-sulfur petroleum coke; wherein the weight of the sulfur in the calcined high-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined high-sulfur petroleum coke;

[0136] S2. The medium-sulfur petroleum coke is subjected to a second pre-calcination to reduce the sulfur content of the medium-sulfur petroleum coke to obtain calcined medium-sulfur petroleum coke; wherein the weight of sulfur in the calcined medium-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined medium-sulfur petroleum coke;

[0137] S301. The calcined high-sulfur petroleum coke is first crushed and first screened to obtain calcined high-sulfur petroleum coke coarse particles and calcined high-sulfur petroleum coke fine particles, respectively;

[0138] S302. The calcined medium-sulfur petroleum coke is subjected to a second crushing and a second screening to obtain calcined medium-sulfur petroleum coke particles and calcined medium-sulfur petroleum coke powder, respectively;

[0139] S401. The calcined high-sulfur petroleum coke coarse particles, the calcined high-sulfur petroleum coke fine particles and the calcined medium-sulfur petroleum coke particles are mixed to obtain aggregate coke particles;

[0140] S402. The calcined sulfur petroleum coke powder is stirred and dispersed to obtain a powder;

[0141] S403. The aggregate char particles and powder are mixed at 150°C to obtain a dry material;

[0142] S5. The binder and the dry material are mixed at 175° C. to obtain a cathode raw material;

[0143] S6. The cathode raw material is molded to obtain a cathode raw material block; and

[0144] S701. The cathode raw material block is subjected to a first round of calcination to obtain a primary cathode calcined block;

[0145] S702. The primary cathode calcined block is subjected to a second round of calcination to obtain a cathode calcined block;

[0146] S703. Graphitize the cathode calcined block to obtain a graphitized cathode carbon block.

[0147] The heating rate of the first calcination is 4°C / min, the temperature of the first pre-calcination is 1400°C, and the time of the first pre-calcination is 3h;

[0148] The heating rate of the second calcination is 4°C / min, the temperature of the second pre-calcination is 1300°C, and the time of the second pre-calcination is 3h.

[0149] The weight of sulfur in the high-sulfur petroleum coke is 3% to 7% of the total weight of the high-sulfur petroleum coke;

[0150] The weight of sulfur in the medium-sulfur petroleum coke is 1.5% to 3.0% of the total weight of the medium-sulfur petroleum coke.

[0151] The weight of sulfur in the calcined high-sulfur petroleum coke is 0.47% of the total weight of the calcined high-sulfur petroleum coke, and the true density of the calcined high-sulfur petroleum coke is 2.07 g / cm 3 ;

[0152] The weight of sulfur in the calcined medium-sulfur petroleum coke is 0.39% of the total weight of the calcined medium-sulfur petroleum coke, and the true density of the calcined medium-sulfur petroleum coke is 2.05 g / cm 3 .

[0153] The weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=17:20:33:100;

[0154] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=30:100.

[0155] The average particle size of the calcined high-sulfur petroleum coke coarse particles is 5mm to 8mm;

[0156] The average particle size of the calcined high-sulfur petroleum coke fine particles is 2mm to 5mm;

[0157] The average particle size of the calcined medium-sulfur petroleum coke particles is 0.3 mm to 2.0 mm;

[0158] The average particle size of calcined medium-sulfur petroleum coke powder is ≤0.3mm;

[0159] The binder includes coal tar; the added amount of the binder m6 and the total weight of the dry material m4 satisfy the relationship: m6:m4=17:100.

[0160] The temperature of the first round of calcination was 1000°C and the time of the first round of calcination was 550h;

[0161] The temperature of the second round of calcination is 900°C, and the time of the second round of calcination is 360h;

[0162] The temperature of the graphitization treatment is 2700°C, and the time of the graphitization treatment is 25h.

[0163] The molding process includes kneading and vibration molding, wherein the kneading temperature is 170°C and the kneading time is 40 minutes;

[0164] The temperature of vibration molding is 160°C, and the time of vibration molding is 3 minutes.

[0165] Example 2

[0166] Based on the contents disclosed in Example 1, the following modifications are further made:

[0167] S305. The aggregate char and powder are mixed at 155°C to obtain a dry material;

[0168] S4. Mixing the binder and the dry material at 180° C. to obtain a cathode raw material;

[0169] The temperature of the first pre-baking is 1500°C;

[0170] The temperature of the second pre-baking is 1350°C.

[0171] The weight of sulfur in the calcined high-sulfur petroleum coke is 0.49% of the total weight of the calcined high-sulfur petroleum coke, and the true density of the calcined high-sulfur petroleum coke is 2.08 g / cm 3 ;

[0172] The weight of sulfur in the calcined medium-sulfur petroleum coke is 0.41% of the total weight of the calcined medium-sulfur petroleum coke, and the true density of the calcined medium-sulfur petroleum coke is 2.06 g / cm 3 .

[0173] The weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=19:20:31:100;

[0174] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=30:100.

[0175] The average particle size of the calcined high-sulfur petroleum coke coarse particles is 5mm to 8mm;

[0176] The average particle size of the calcined high-sulfur petroleum coke fine particles is 2mm to 5mm;

[0177] The average particle size of the calcined medium-sulfur petroleum coke particles is 0.3 mm to 2.0 mm;

[0178] The average particle size of calcined medium-sulfur petroleum coke powder is ≤0.3mm.

[0179] The amount of binder added m6 and the total weight of dry material m4 satisfy the relationship: m6:m4=18:100.

[0180] The temperature of the first round of roasting was 1020°C and the time of the first round of roasting was 540h;

[0181] The temperature of the second round of roasting is 920℃, and the time of the second round of roasting is 370h;

[0182] The temperature of the graphitization treatment is 2750°C, and the time of the graphitization treatment is 25h.

[0183] The kneading temperature was 185°C and the kneading time was 40 min;

[0184] The temperature of vibration molding is 165°C, and the time of vibration molding is 2.5 minutes.

[0185] Example 3

[0186] Based on the contents disclosed in Example 1, the following modifications are further made:

[0187] S305. The aggregate char and powder are mixed at 155°C to obtain a dry material;

[0188] S4. Mixing the binder and the dry material at 175° C. to obtain a cathode raw material;

[0189] The temperature of the first pre-baking is 1600°C;

[0190] The temperature of the second pre-baking is 1300°C.

[0191] The weight of sulfur in the calcined high-sulfur petroleum coke is 0.52% of the total weight of the calcined high-sulfur petroleum coke, and the true density of the calcined high-sulfur petroleum coke is 2.08 g / cm 3 ;

[0192] The weight of sulfur in the calcined medium-sulfur petroleum coke is 0.39% of the total weight of the calcined medium-sulfur petroleum coke, and the true density of the calcined medium-sulfur petroleum coke is 2.05 g / cm 3 .

[0193] The weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=17:21:31:100;

[0194] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=31:100.

[0195] The average particle size of the calcined high-sulfur petroleum coke coarse particles is 5mm to 8mm;

[0196] The average particle size of the calcined high-sulfur petroleum coke fine particles is 2mm to 5mm;

[0197] The average particle size of the calcined medium-sulfur petroleum coke particles is 0.3 mm to 2.0 mm;

[0198] The average particle size of calcined medium-sulfur petroleum coke powder is ≤0.3mm.

[0199] The amount of binder added m6 and the total weight of dry material m4 satisfy the relationship: m6:m4=16.5:100.

[0200] The temperature of the first round of calcination was 1050°C and the time of the first round of calcination was 530h;

[0201] The temperature of the second round of calcination is 900°C, and the time of the second round of calcination is 380h;

[0202] The temperature of the graphitization treatment is 2700°C, and the time of the graphitization treatment is 27h.

[0203] The kneading temperature was 185°C and the kneading time was 45 min;

[0204] The temperature of vibration molding is 165°C, and the time of vibration molding is 5 minutes.

[0205] Example 4

[0206] Based on the contents disclosed in Example 1, the following modifications are further made:

[0207] S305. The aggregate char and powder are mixed at 160°C to obtain a dry material;

[0208] S4. Mixing the binder and the dry material at 170° C. to obtain a cathode raw material;

[0209] The first pre-baking temperature is 1550°C;

[0210] The temperature of the second pre-baking was 1350°C.

[0211] The weight of sulfur in the calcined high-sulfur petroleum coke is 0.50% of the total weight of the calcined high-sulfur petroleum coke, and the true density of the calcined high-sulfur petroleum coke is 2.08 g / cm 3 ;

[0212] The weight of sulfur in the calcined medium-sulfur petroleum coke is 0.40% of the total weight of the calcined medium-sulfur petroleum coke, and the true density of the calcined medium-sulfur petroleum coke is 2.06 g / cm 3 .

[0213] The weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=18:21:30:100;

[0214] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=31:100.

[0215] The average particle size of the calcined high-sulfur petroleum coke coarse particles is 5mm to 8mm;

[0216] The average particle size of the calcined high-sulfur petroleum coke fine particles is 2mm to 5mm;

[0217] The average particle size of the calcined medium-sulfur petroleum coke particles is 0.3 mm to 2.0 mm;

[0218] The average particle size of calcined medium-sulfur petroleum coke powder is ≤0.3mm.

[0219] The amount of binder added m6 and the total weight of dry material m4 satisfy the relationship: m6:m4=18:100.

[0220] The temperature of the first round of calcination was 1050°C and the time of the first round of calcination was 600h;

[0221] The temperature of the second round of calcination is 950°C, and the time of the second round of calcination is 350h;

[0222] The temperature of the graphitization treatment is 2750°C, and the time of the graphitization treatment is 20 hours.

[0223] The kneading temperature was 170°C and the kneading time was 30 min;

[0224] The temperature of vibration molding is 160°C, and the time of vibration molding is 4 minutes.

[0225] Comparative Example 1

[0226] Based on the contents disclosed in Example 1, the following modifications are further made:

[0227] Without performing the first pre-calcination and the second pre-calcination, low-sulfur petroleum coke is directly used to replace the calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke.

[0228] The pre-calcination temperature of low-sulfur petroleum coke is 1250°C, the pre-calcination heating rate is 4°C / min, and the pre-calcination time is 3h.

[0229] The weight of sulfur in the calcined low-sulfur petroleum coke is 0.44% of the total weight of the calcined low-sulfur petroleum coke, and the true density is 2.06 g / cm 3 .

[0230] Then, according to the method disclosed in Example 1, calcined low-sulfur petroleum coke coarse particles with a particle size of 5mm-8mm, calcined low-sulfur petroleum coke medium particles with a particle size of 2mm-5mm, calcined low-sulfur petroleum coke fine particles with a particle size of 0.3mm-2.0mm and calcined low-sulfur petroleum coke powder with a particle size of 0.3mm were prepared in sequence, and the calcined petroleum coke particles were fully mixed at 160°C in a mass ratio of 16:23:30:31 to obtain a dry material, and then a binder was added at 170°C and a graphitized cathode carbon block was prepared according to the method of Example 1.

[0231] The amount of binder added m6 and the total weight of dry material m4 satisfy the relationship: m6:m4=18:100.

[0232] The temperature of the first round of calcination was 1050°C and the time of the first round of calcination was 600h;

[0233] The temperature of the second round of calcination is 950°C and the time of the second round of calcination is 400h;

[0234] The temperature of the graphitization treatment is 2750°C, and the time of the graphitization treatment is 30 hours.

[0235] The kneading temperature was 175°C and the kneading time was 45 min;

[0236] The temperature of vibration molding is 165°C, and the time of vibration molding is 5 minutes.

[0237] Comparative Example 2

[0238] Based on the content disclosed in Example 1, the following modifications are further made:

[0239] The temperature of the first pre-baking is 1000°C, and the time of the first pre-baking is 6 hours;

[0240] The temperature of the second pre-baking is 1200° C., and the time of the second pre-baking is 6 hours.

[0241] Comparative Example 3

[0242] Based on the content disclosed in Example 1, the following modifications are further made:

[0243] The temperature of the first pre-baking is 1800°C, and the time of the first pre-baking is 1h;

[0244] The temperature of the second pre-baking is 1500° C., and the time of the second pre-baking is 1 hour.

[0245] Comparative Example 4

[0246] Based on the content disclosed in Example 1, the following modifications are further made:

[0247] The weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=10:30:35:100;

[0248] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=25:100.

[0249] Comparative Example 5

[0250] Based on the content disclosed in Example 1, the following modifications are further made:

[0251] The weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=30:10:20:100;

[0252] The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=40:100.

[0253] Related experiments and effect data:

[0254] The compressive strength and resistivity of the graphitized cathode carbon blocks obtained in each embodiment and comparative example were statistically analyzed, and the results are shown in Table 1.

[0255] Table 1 Compressive strength and resistivity of graphitized cathode carbon blocks of various embodiments and comparative examples

[0256]

[0257] As can be seen from Table 1, a method for preparing a graphitized cathode provided in an embodiment of the present application, the preparation method processes high-sulfur petroleum coke and medium-sulfur petroleum coke respectively by a first calcination and a second calcination to remove sulfur from the two, and then forms a stable, low-sulfur weight content and high-strength embedded structure through the bonding effect of a binder after subsequent crushing and mixing, and a dense carbide can be formed in subsequent gradient roasting and graphitization treatment, thereby increasing the strength of the graphitized cathode carbon block to 23MPa or above; in addition, the produced graphitized cathode carbon block also has a lower resistance (<10μΩ·m), which can effectively reduce the heat generated during the use of the electrolytic cell, thereby extending the service life of the graphitized cathode in the electrolytic cell.

[0258] In addition, an embodiment of the present application provides a method for preparing a graphitized cathode, which can produce high-strength graphitized cathode carbon blocks, thereby extending the service life of the graphitized cathode in the electrolytic cell; in addition, the graphitized cathode carbon blocks produced by this method also have lower resistance, which may be due to the formation of dense carbides that reduce the resistance between the graphitized cathode carbon block particles, which greatly promotes the improvement of various technical and economic indicators of large-scale cell production.

[0259] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.

Claims

1. A method for preparing a graphitized cathode, the method comprising: The high-sulfur petroleum coke is subjected to a first pre-calcination to reduce the sulfur content of the high-sulfur petroleum coke to obtain calcined high-sulfur petroleum coke; wherein the weight of the sulfur in the calcined high-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined high-sulfur petroleum coke; The medium-sulfur petroleum coke is subjected to a second pre-calcination to reduce the sulfur content of the medium-sulfur petroleum coke to obtain calcined medium-sulfur petroleum coke; wherein the weight of the sulfur in the calcined medium-sulfur petroleum coke is less than or equal to 0.8% of the total weight of the calcined medium-sulfur petroleum coke; The calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke are crushed respectively; The crushed calcined high-sulfur petroleum coke and the crushed calcined medium-sulfur petroleum coke are mixed to obtain a dry material containing aggregate coke particles and powder; Mixing the binder and the dry material to obtain a cathode raw material; Forming the cathode raw material to obtain a cathode raw material block; and The cathode raw material block is subjected to gradient calcination and graphitization treatment to obtain a graphitized cathode carbon block.

2. The preparation method according to claim 1, wherein the temperature of the first pre-baking is 1400° C. to 1600° C., and the time of the first pre-baking is 2 h to 4 h; and / or The temperature of the second pre-baking is 1300° C. to 1350° C., and the time of the second pre-baking is 2 h to 4 h.

3. The preparation method according to claim 1, wherein the weight of sulfur in the high-sulfur petroleum coke is 3% to 7% of the total weight of the high-sulfur petroleum coke; and / or The weight of sulfur in the medium-sulfur petroleum coke is 1.5% to 3.0% of the total weight of the medium-sulfur petroleum coke.

4. The preparation method according to claim 1, wherein the calcined high-sulfur petroleum coke and the calcined medium-sulfur petroleum coke are crushed separately, comprising the steps of: The calcined high-sulfur petroleum coke is subjected to a first crushing and a first screening to obtain calcined high-sulfur petroleum coke coarse particles and calcined high-sulfur petroleum coke fine particles, respectively; The calcined medium-sulfur petroleum coke is subjected to a second crushing and a second screening to obtain calcined medium-sulfur petroleum coke particles and calcined medium-sulfur petroleum coke powder, respectively.

5. The preparation method according to claim 4, wherein the average particle size of the calcined high-sulfur petroleum coke coarse particles is 5 mm to 8 mm; and / or The average particle size of the calcined high-sulfur petroleum coke fine particles is 2 mm to 5 mm; and / or The average particle size of the calcined sulfur petroleum coke particles is 0.3 mm to 2.0 mm; and / or The average particle size of the calcined sulfur petroleum coke powder is ≤0.3 mm.

6. The preparation method according to claim 4, wherein the crushed calcined high-sulfur petroleum coke and the crushed calcined medium-sulfur petroleum coke are mixed to obtain a dry material containing aggregate coke particles and powder, comprising the steps of: The calcined high-sulfur petroleum coke coarse particles, the calcined high-sulfur petroleum coke fine particles and the calcined medium-sulfur petroleum coke particles are mixed to obtain aggregate coke particles; Stirring and dispersing the calcined medium-sulfur petroleum coke powder to obtain a powder; The aggregate char particles and the powder are mixed to obtain dry material.

7. The preparation method according to claim 6, wherein the weight m1 of the calcined high-sulfur petroleum coke coarse particles, the weight m2 of the calcined high-sulfur petroleum coke fine particles, the weight m3 of the calcined medium-sulfur petroleum coke particles and the total weight m4 of the dry material satisfy the relationship: m1:m2:m3:m4=(15-20):(20-25):(30-35):100; and / or The weight m5 of the calcined sulfur petroleum coke powder and the total weight m4 of the dry material satisfy the relationship: m5:m4=(30-35):100; and / or The binder includes coal tar; and / or The added amount m6 of the binder and the total weight m4 of the dry material satisfy the relationship: m6:m4=(16-18):

100.

8. The preparation method according to claim 1, wherein the cathode raw material block is subjected to gradient calcination and graphitization treatment to obtain a graphitized cathode carbon block, comprising the steps of: The cathode raw material block is subjected to a first round of calcination to obtain a primary cathode calcined block; The primary cathode calcined block is subjected to a second round of calcination to obtain a cathode calcined block; The cathode calcined block is graphitized to obtain a graphitized cathode carbon block.

9. The preparation method according to claim 8, wherein the temperature of the first round of calcination is 1000°C to 1050°C, and the time of the first round of calcination is 500h to 600h; and / or The temperature of the second round of calcination is 900° C. to 950° C., and the time of the second round of calcination is 350 h to 400 h; and / or The temperature of the graphitization treatment is 2600° C. to 2800° C., and the time of the graphitization treatment is 20 h to 30 h.

10. The preparation method according to claim 1, wherein the molding process comprises kneading and vibration molding; wherein, The kneading temperature is 170°C to 185°C, and the kneading time is 30min to 60min; and / or The temperature of the vibration molding is 160° C. to 165° C., and the time of the vibration molding is 2 min to 5 min.

Citation Information

Cited By

  • Carbon electrode process control method and system

    CN122088753A